Compelled to Compete: Chinese graduates on employment and social mobility after international and domestic study. (July 2021) - Zhai, Keyu; Moskal, Marta; Read, Barbara
Highlights: International graduates are believed to enjoy substantial advantages compared with domestic graduates in China. Both domestic and international graduates perceived that international graduate have more career opportunities. Domestic graduates, however, reported not only positive employment outcomes but upward social mobility. Women, both international and domestic graduates, are disadvantaged in labour market in comparison to men. China's societal institutions, defuse to some extent social tensions arising from increasing labour market competition. Abstract: The article offers unique insights into international and domestic graduates' career progression and social mobility experiences in China. Drawing on in-depth interview data with master-level graduates, the analytical results reveal that the majority of the participants (both domestic and international) perceive that international graduates have more opportunities and better career progression, but the analytical results show that both domestic and international graduates secured positive employment outcomes. Significant gender disparities exist, as women, both international and domestic graduates, are still disadvantaged in terms of occupational attainment and career prospects and report lower employment satisfaction. All domestic graduates reported not only positive employment outcomes in the labour market but upward social mobility. In contrast, the majority of international graduates reported not having achieved the same level of social status as their parents. Graduates' differentiated relations to China's state institutions of Bianzhi, Danwei and Hukou and social connections ( Guanxi ) heavily influenced their employment trajectories and social mobility. We argue that the participants' conflicting perceptions are linked to the intense labour market competition encouraged by the sustained expansion of domestic higher education enrolment and amplified by the increasing number of international graduates. The societal institutions defuse to some extent conflicts over economic interests arising from the marketisation of social life.